2014
DOI: 10.1021/np400776y
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic Phenolic Ethers from Trichobotrys effusa

Abstract: Four novel aliphatic phenolic ethers, namely, trichoethers A-D (1-4), possessing a unique C11-O-C10 skeleton, together with coriloxin, zythiostromic acid A, radicicol, and 3,5-dihydroxytoluene were isolated from the ethyl acetate extracts of the fermented broths of Trichobotrys effusa YMJ1179. The structures of all the compounds were determined based on spectroscopic data analysis. The configurations of 1-4 were established by J values and NOESY and compared with published data. Compounds 1-4 and radicicol exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Based on ITS, LSU, SSU and tef1-α sequence comparison with the GenBank database, similar species in Dictyosporiaceae were found. The sequences of 37 relevant species according to the blasting result and recent publications ( Tanaka and Harada 2003 ; Chen et al 2014 ; Tanaka et al 2015 ; Boonmee et al 2016 ; Liu et al 2017 ; Yang et al 2018a ; Chen et al 2020 ) were chosen for phylogenetic analyses (Table 1 ) and were downloaded from GenBank. Four gene regions (ITS, LSU, SSU and tef1-α ) were individually aligned using the online service of MAFFT v. 7 ( Madeira et al 2019 ) and concatenated using PhyloSuite v. 1.2.2 ( Zhang et al 2020 ).…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on ITS, LSU, SSU and tef1-α sequence comparison with the GenBank database, similar species in Dictyosporiaceae were found. The sequences of 37 relevant species according to the blasting result and recent publications ( Tanaka and Harada 2003 ; Chen et al 2014 ; Tanaka et al 2015 ; Boonmee et al 2016 ; Liu et al 2017 ; Yang et al 2018a ; Chen et al 2020 ) were chosen for phylogenetic analyses (Table 1 ) and were downloaded from GenBank. Four gene regions (ITS, LSU, SSU and tef1-α ) were individually aligned using the online service of MAFFT v. 7 ( Madeira et al 2019 ) and concatenated using PhyloSuite v. 1.2.2 ( Zhang et al 2020 ).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Petch from Sri Lanka, which was placed in Pleosporales genera incertae sedis ( Pleosporales , Dothideomycetes , Ascomycota ) ( Petch 1924 ; Morgan-Jones et al 1987 ). Trichobotrys effusa is known for producing compounds which can exhibit significant growth-inhibitory activities against the A549 lung cancer cell line ( Chen et al 2014 ). In addition, the bioactive compounds obtained from the deep-sea-derived fungus T. effusa DEFSCS021 could strongly inhibit the larvae settlement of Bugula neritina and Balanus amphitrite larvae ( Sun et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study observed that ethyl acetate extract from the fermented broth of T. effusa YMJ1179 inhibited the growth of A549 lung cancer cells [ 7 ]. Coriloxin, an antimicrobial metabolite, has been isolated from this fermented broth [ 8 , 9 ]. Furthermore, coriloxin has been isolated from various xylariaceous, endophytic fungi, including strains YUA-026, Xylaria sp.…”
Section: Introductionmentioning
confidence: 99%
“…Diene (50) was first furnished through HWE reaction between aldehyde (48) and phosphonate ester (49) before reducing the ester moiety to attain alcohol (51). The second intermediate was then prepared through Wittig olefination between aldehyde (52) and ylide (53) using a strong base n-BuLi to give triene (54). A series of chemical transformations were then performed with the removal of the acetonide protecting group, followed by the protection of the secondary chiral alcohol to prevent decomposition of the diol due to the conjugated nature of the molecule.…”
Section: Horner-wadsworth-emmons Reactionmentioning
confidence: 99%
“…The family of trichoether natural products was first isolated in 2014 from the deuteromycetous fungus Trichobotrys effusa in Taiwan. 52 Encompassing only one stereogenic centre, trichoether B possesses both an aldehyde and a ketone on the skeleton of the molecule. However, with the optical rotation found to be close to 0, the stereochemistry at the ether position was elucidated to be in its racemate form.…”
Section: Background Of the Trichoether Familymentioning
confidence: 99%